Teachers' Efforts to Increase Students' Creativity in Mixed Ensembles in Class X SMAN 3 Padangpanjang - Zikri, Afriza Aidil; Syeilendra, Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study is to describe the teacher's efforts in increasing student creativity in class X mixed material of Science 1 SMAN 3 Padangpanjang. This type of research uses qualitative research using descriptive methods. The stage of application of cultural arts learning consists of 2 learnings, namely. 45 minutes per hour. Which is divided into three activities consisting of 15 minutes of opening or opening activities, 60 minutes of core activities and 15 minutes of closing or closing activities. Learning went well. However, when applied in the classroom, researchers observed a difference, namely the lack of student discipline in the implementation of learning, causing some students not to understand the previously completed learning until the teacher had to explain. prior learning so that students really understand the whole mix.